Investigation and Characterization of Pickering Emulsion Stabilized by Alkali-Treated Zein (AZ)/Sodium Alginate (SA) Composite Particles - Kuang, Ying; Xiao, Qinjian; Yang, Yichen; Liu, Menglong; Wang, Xiaosa; Deng, Pengpeng; Wu, Kao; Liu, Yi; Peng, Bo; Jiang, Fatang; Li, Cao (Materials, 2023)
Pickering emulsions stabilized by food-grade colloidal particles have attracted increasing attention in recent years due to their “surfactant-free” nature. In this study, the alkali-treated zein (AZ) was prepared via restricted alkali deamidation and then combined with sodium alginate (SA) in different ratios to obtain AZ/SA composite particles (ZS), which were used to stabilize Pickering emulsion. The degree of deamidation (DD) and degree of hydrolysis (DH) of AZ were 12.74% and 6.58% respectively, indicating the deamidation occurred mainly in glutamine on the side chain of the protein. After the treatment with alkali, AZ particle size decreased significantly. Moreover, the particle size of ZS with different ratios was all less than 80 nm. when the AZ/SA ratio was 2:1(Z2S1) and 3:1(Z3S1), the three-phase contact angle (θo/w) were close to 90°, which was favorable for stabilizing the Pickering emulsion. Furthermore, at a high oil phase fraction (75%), Z3S1-stabilized Pickering emulsions showed the best long-term storage stability within 60 days. Confocal laser scanning microscope (CLSM) observations showed that the water-oil interface was wrapped by a dense layer of Z3S1 particles with non-agglomeration between independent oil droplets. At constant particle concentration, the apparent viscosity of the Pickering emulsions stabilized by Z3S1 gradually decreased with increasing oil phase fraction, and the oil-droplet size and the Turbiscan stability index (TSI) also gradually decreased, exhibiting solid-like behavior. This study provides new ideas for the fabrication of food-grade Pickering emulsions and will extend the future applications of zein-based Pickering emulsions as bioactive ingredient delivery systems.